The Effectiveness Of Halal Labels As Moderated Variables Influence Between Product Quality, Brand Image, And Wom To Decisions On Purchase Of FAZZA Drinking Water Products - Mochamad Fatikhudin; Suwignyo Widagdo; Agustin Hari Prastyowati (ABM: International Journal of Administration, Business and Management, 2021)
This study aims to determine the effect of product quality, brand image, and WOM on Fazza's (Drinking Water Product) purchasing decisions with a halal label as a moderating variable. The population in this study were all consumers of Fazza Product located in Lumajang Regency. The sample selection method uses a purposive sampling method and obtained a sample amount of 100 respondents. The method of data collection is done by questionnaire, interview, observation and literature study. The data analysis technique used in this study is the moderated regression analysis technique or MRA. The results showed that product quality, brand image, and WOM significantly influenced the purchase decision of Fazza Drinking Water Product. While the halal label cannot be moderated or doesn't play a role in strengthening the influence relationship between product quality, brand image, and WOM on the purchase decision of Fazza Drinking Water Product. The magnitude of the coefficient of initial determination (R square) is equal to 0.522 or 52.2%. This means that 52.2 % of the variation changes dependent variable is the purchase decision can be explained by the three independent variables which are product quality, brand image, and WOM, while the remaining 47.8% is explained by other causes beyond the model. Keywords: product quality, brand image, WOM, halal label and purchasing decisions.